A comparison between high‐intensity focused ultrasound and surgical treatment for the management of abdominal wall endometriosis. (30th August 2017) - Zhu, X; Chen, L; Deng, X; Xiao, S; Ye, M; Xue, M
Abstract : Objective: The aim of this study was to compare the therapeutic outcomes of high‐intensity focused ultrasound (HIFU) and surgical treatment for abdominal wall endometriosis. Design: A retrospective study. Setting: Gynaecological department of a teaching hospital in China. Population: Patients with abdominal wall endometriosis. Methods: Among the 51 patients, 23 patients were treated with ultrasound‐guided HIFU and 28 patients with surgery. Pain relief and the size change of the nodule after each management were evaluated 1, 3, 6 and 12 months after treatment, respectively. The hospital stay and blood loss were also compared. Main outcome measures: Difference between HIFU and surgical treatment for abdominal wall endometriosis. Results: No statistically significant differences were observed between the two groups in the pain relief in 1, 3, 6 and 12 months after treatment, respectively. The hospital stay was clearly shorter in the HIFU group than in the surgery group. Change in nodules was more remarkable in the group treated with surgery; no palpable nodules existed in most patients in the surgery group. HIFU had more advantages over surgery, such as no blood loss, no new scar, no anaesthesia and lower pain score immediately after treatment. Conclusions: Based on our results, it appears that either HIFU or surgery is safe and effective in treating patients with AWE in short‐term. Compared with surgery, HIFU treatment for AWE has the advantages of shorter hospital stay, no blood loss, no new scar, no anaesthesia and a lower immediate pain score. Tweetable abstract: Either HIFU or surgical treatment is safe and effective in treating patients with AWE. HIFU has the advantages of a less invasive procedure and shorter hospital stay. Tweetable abstract: Either HIFU or surgical treatment is safe and effective in treating patients with AWE. HIFU has the advantages of a less invasive procedure and shorter hospital stay.